Androgen signaling in the placenta - Cleys, Ellane Rachael, author; Bouma, Gerrit, advisor; Clay, Colin, advisor; Tobet, Stuart, committee member; Di Pietro, Santiago, committee member (Colorado State University. Libraries, 2014)
Placental estrogen signaling is known to regulate placental trophoblast function and differentiation. However, the role of placental androgen signaling has never been investigated, despite the rise of maternal serum androgens throughout gestation. Recent findings have shown increased maternal serum androgen in patients with the placental induced disorder preeclampsia. Preeclampsia, a maternal hypertension and proteinuria condition instigated by insufficient trophoblast differentiation and invasion into maternal spiral arteries, is also associated with increased placental expression of androgen receptor and an increased risk of incidence in patients with polymorphisms in androgen receptor that decrease androgen signaling. These findings suggest a crucial role for placental androgen signaling. Moreover, research investigating androgen's role in cancer progression has shown that many androgen responsive genes regulate cell proliferation, differentiation to invasive phenotypes, and tissue vascularization, all processes necessary for normal placental development. Androgen signaling in tumor tissues is further regulated by androgen receptor complexes with histone lysine demethylases. These complexes are recruited to androgen response elements in DNA and dynamically regulate histone tail modifications for transcription initiation. This led us to the overall hypothesis that (1) androgen signaling in trophoblast cells is important for placental development, and (2) androgen receptor complexes with histone lysine demethylases in the placenta to regulate vascularization, growth and invasion factors in trophoblast cells. To test this hypothesis, we utilized a prenatal androgenization ewe model as well as human first trimester placental samples and immortalized human trophoblast cell lines. Using the prenatal androgenized ewe model, we report for the first time expression of histone lysine demethylases in the placenta. Furthermore, we showed androgen receptor complexes with histone lysine demethylases and is recruited to an androgen response elements in the 5'untranslated flanking sequence of vascular endothelial growth factor in the sheep placenta. We also report that histone lysine demethylase are present in human first trimester syncytiotrophoblast and complex with androgen receptor in immortalized trophoblasts. Additionally, we demonstrated that androgen receptor complexes with histone lysine demethylases are also present in choriocarcinoma ACH-3P and BeWo cells. Dihydrotestosterone treatment in these cells led to down-regulation of androgen responsive genes, specifically KDM3A and MMP2. Inhibition of androgen receptor through flutamide treatment altered mRNA levels for genes regulating vascularization, including HIF1α, PPARα, and PPARy. Hypoxia also decreased CYP19 levels, however, further investigation is needed to confirm dihydrotestosterone and flutamide effect on protein expression in trophoblast cells. These data suggest that histone lysine demethylases complex with androgen receptor to regulate androgen responsive genes, including those directing placental vascularization and development. However, further experiments are needed to confirm the necessity of histone lysine demethylases for targeted androgen signaling in trophoblast cells and to determine if androgen directly regulates trophoblast differentiation and invasion. These findings suggest androgen signaling may play a critical role in placental development.
Keywords: histone lysine demethylases; trophoblast; preeclampsia; androgen; placenta